PENGEMBANGAN PERANGKAT PERCOBAAN REFRAKSI CAHAYA SEBAGAI MEDIA PEMBELAJARAN IPA FISIKA SMP - Noer Iskandar; Yennita Yennita; Muhammad Syafi’i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to produce a valid and practical light refraction device so that it is feasible to be used as a learning media for junior high school science. This research method is Research and Development (R & D) with the ADDIE (Analysis-Design-Development-Implication-Evaluation) development model. The object of this research is a trial device consisting of a light refraction experiment tool and student worksheets. The research data was obtained from the results of validation by 3 lecturers of physics education study programs, 2 junior high school science teachers as validators and 10 student. Validation is carried out through two stages, stage I of the validation is improvement and stage 2 of the validation is subsequent assessment after the device is declared valid, the device is tested on a limited basis to see the practicality of the device. Data were analyzed descriptively to determine the value of the practical validity of the experimental device. The results of data analysis obtained : the validation of the experiment tool 3.74 with very valid validity level and the assessment of the experiment student worksheet 3.82 with a very valid validity level, the practical assessment of the 3.56 experiment tool with the very practical category and the assessment of the worksheet experimental students 3.61 in a very practical category. Based on the data analysis, it can be concluded that the light refraction experiment device developed can be declared valid and practical so that it is feasible to be used as a learning medium for Junior High School science.Keyword: Development, Trial Device, Light Refraction.